Khulafah Al- Rasyidun: Masa Kepemimpinan Ali bin Abi Thalib - Hamzah, Saidin; Hamriana (Program Studi Sejarah Peradaban Islam, 2023)
The aims of this research are 1) to examine and analyze the procession of appointing Ali bin Abi Talib; 2) Review and analyze the government system of Caliph Ali bin Abi Talib; 3) Reconstructing the political upheaval during the time of Ali bin Abi Talib. This study uses historical methods to reconstruct events with heuristics, source criticism, interpretation, and historiography as the last stage of research activities. The results of this study indicate that the Caliphate of Ali bin Abi Talib is a caliphate that intends to embody the messages of the Prophet that he obtained while with him. He contributed a lot and defended Islam from many enemies. Proficient in war strategy and having difficulty in controlling the state administration which is in a state of chaos. Confrontation from various parties (Khawarij, Thalha and Mu'awiyah) is evidence of the heartbreaking history of Islam because it is more driven by material motives than humanity and religion. Tujuan penelitian ini adalah 1) mengkaji dan menganalisis prosesi pengangkatan Ali bin Abi Thalib; 2) Mengkaji dan mengalisis sistem pemerintahan Khalifah Ali bin Abi Thalib; 3) Merekontruksi pergolakan politik masa Ali bin Abi Thalib. Penelitian ini menggunakan metode sejarah untuk merekonstruksi peristiwa dengan heuristik, kritik sumber, interpretasi, dan historiografi sebagai tahap terakhir dari kegiatan penelitian. Hasil penelitian ini menunjukkan bahwa Kekhalifaan Ali bin Abi Thalib adalah kekhalifaan yang bermaksud mengejawantahkan pesan-pesan Rasulullah yang dia peroleh selama bersamanya. Ia banyak memberikan sumbangsi dan mempertahankan Islam dari banyak musuh. Mahir dalam strategi perang dan mengalami kesulitan dalam mengendalikan administrasi negara yang dalam keadaan caos. Konfrontasi dari berbagai pihak (Khawarij, Thalha dan Mu’awiyah) adalah bukti sejarah Islam yang memilukan karena lebih banyak tergerakkan oleh motif-motif material ketimbang kemanusiaan dan agama.